2020
DOI: 10.1111/jrh.12420
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Impact of Cancer: Differences in Rural and Nonrural Non‐Hodgkin's Lymphoma Survivors

Abstract: Purpose People living in rural areas experience greater health disparities than their nonrural counterparts, but little is known about the association between rural status and quality of life (QOL) in non‐Hodgkin's lymphoma (NHL) survivors. We compared self‐reported quality of life and impact of cancer in rural and nonrural NHL survivors. Methods This study is a secondary analysis of 566 NHL cancer survivors recruited from cancer registries at 2 large academic medical centers in 1 state. Standardized measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
7
2
Order By: Relevance
“…Some survivors had physical complaints which impacted their daily lives; others felt an indescribable change in how they physically felt 63 . Survivors with active disease, long‐term disease, comorbidities, of older age or rural residence were associated with worse physical functioning 56,68,69,71 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some survivors had physical complaints which impacted their daily lives; others felt an indescribable change in how they physically felt 63 . Survivors with active disease, long‐term disease, comorbidities, of older age or rural residence were associated with worse physical functioning 56,68,69,71 …”
Section: Resultsmentioning
confidence: 99%
“…63 Survivors with active disease, long-term disease, comorbidities, of older age or rural residence were associated with worse physical functioning. 56,68,69,71 Cancer-related fatigue persistently affects individuals with lymphoma and impacts quality of life. 39,55,72 General practitioner visits were higher (almost double) for participants experiencing severe cancer-related fatigue than those without severe fatigue.…”
Section: Impactful and Debilitating Concernsmentioning
confidence: 99%
“…Regarding lymphoma care, numerous studies have reported the influence of social inequalities, particularly on mortality and morbidity [8,9]. Although studies on the relationship between SES and HRQoL among lymphoma survivors have slowly increased in recent years [10][11][12], most investigations on this relationship were collected solely through patients' self-reported data. In clinical practice, when cancer patients are in poor physical or mental health and are unable to respond, proxies are asked to report on the patient's behalf [13]; however, the impact of proxy reports on HRQoL in surveys has rarely been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…This may be further exacerbated by additional challenges including greater travel distance to receive treatment, limited access to health and care facilities and to bespoke or individually tailored support [ 22 ]. Research also suggests that people with cancer from rural communities may be at risk of experiencing a reduction in quality of life following the completion of treatment [ 23 ], reflecting the need to provide tailored supportive care to improve their quality of life [ 24 ]. A recent systematic review concluded that rural survivors should be seen as having unique psychosocial needs when compared to urban survivors but not necessarily greater levels of need [ 17 ].…”
Section: Introductionmentioning
confidence: 99%